Design and Implementation of Real-Time Diesel Engine Operational Monitoring Devices Based on Microcontrollers - M. Zaki Latif Abrori; J. Preston Siahaan; Rizqi Ilmal yaqin; Bobby Demeianto; Mula Tumpu; Darmawan Darmawan (Postgraduate, University of Mataram, 2025)
Monitoring of diesel engine operational performance on fishing vessels recorded in real time based on microcontrollers is still rarely used. Monitoring of diesel engine operations is important to ensure the engine is in optimal performance as well as a consideration for predictive maintenance actions. This study aims to design and implement a real-time monitoring device based on microcontrollers. This device can measure and record RPM, temperature, and pressure data on diesel engines with good accuracy. Hall effect sensors for RPM, DS18B20 for temperature, and piezoresistive sensors for pressure are used, to maintain the right time it is equipped with RTC, SD card module for data storage, and Wi-Fi module for data access via the web. The test results show that this device is able to measure with good accuracy on each parameter with an average error of below 2%. When the operational parameters exceed the predetermined threshold, the device successfully gives an alarm as a critical sign. This study makes a significant contribution to the management and maintenance of diesel engines with real-time data and wireless access that increases efficiency and minimizes downtime due to operational failures